Total disc replacement versus anterior cervical discectomy and fusion: a systematic review with meta-analysis of data from a total of 3160 patients across 14 randomized controlled trials with both short- and medium- to long-term outcomes. (August 2018) - Findlay, C.; Ayis, S.; Demetriades, A. K.
Abstract : Aims: The aim of this study was to determine how the short- and medium- to long-term outcome measures after total disc replacement (TDR) compare with those of anterior cervical discectomy and fusion (ACDF), using a systematic review and meta-analysis. Patients and Methods: Databases including Medline, Embase, and Scopus were searched. Inclusion criteria involved prospective randomized control trials (RCTs) reporting the surgical treatment of patients with symptomatic degenerative cervical disc disease. Two independent investigators extracted the data. The strength of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) criteria. The primary outcome measures were overall and neurological success, and these were included in the meta-analysis. Standardized patient-reported outcomes, including the incidence of further surgery and adjacent segment disease, were summarized and discussed. Results: A total of 22 papers published from 14 RCTs were included, representing 3160 patients with follow-up of up to ten years. Meta-analysis indicated that TDR is superior to ACDF at two years and between four and seven years. In the short-term, patients who underwent TDR had better patient-reported outcomes than those who underwent ACDF, but at two years this was typically not significant. Results between four and seven years showed significant differences in Neck Disability Index (NDI), 36-Item Short-Form Health Survey (SF-36) physical component scores, dysphagia, and satisfaction, all favouring TDR. Most trials found significantly less adjacent segment disease after TDR at both two years (short-term) and between four and seven years (medium- to long-term). Conclusion: TDR is as effective as ACDF and superior for some outcomes. Disc replacement reduces the risk of adjacent segment disease. Continued uncertainty remains about degeneration of the prosthesis. Long-term surveillance of patients who undergo TDR may allow its routine use. Cite this article: Bone Joint J 2018;100-B:991–1001.